If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 3 = 51 Reorder the terms: 3 + 8y = 51 Solving 3 + 8y = 51 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8y = 51 + -3 Combine like terms: 3 + -3 = 0 0 + 8y = 51 + -3 8y = 51 + -3 Combine like terms: 51 + -3 = 48 8y = 48 Divide each side by '8'. y = 6 Simplifying y = 6
| (v+7)(v-8)=0 | | -3x=-1(x-6) | | 4x^2-13x+20=4x+5 | | z-344=-245 | | (y-9)(y+3)=0 | | -2(-7n+6)-2(8n+1)=-22 | | f+50=97 | | 3(6-2x)=8x | | 5y^2-27y+10=0 | | 2x+3=34 | | -5g=-20 | | 4.8x+0.2(x-2)=3 | | x^2-16x+9=-4x-2 | | 4x-10=-2x+14 | | 15z^2+16z+4=0 | | 6x+10+14x=5(1+4x) | | 4x+4 -6x=8(x-2) | | 268=69-w | | -8n=80 | | 8x+4y+6=70 | | 2z+5=3z | | -10x+16=-2(5x-8) | | 2x(x+2)=3(x+2) | | 2x^3+9x^2-8x-36=0 | | 23-16=6x-2x+9x | | -6+3Y=3+2Y | | 12z^2-17z-5=0 | | 5x-2=x+85 | | 12x^2-17z-5=0 | | z-6z=9z-6-z | | 5(y-4)/3=2y-2 | | 3-5n=12 |